1998
DOI: 10.1128/jb.180.17.4621-4627.1998
|View full text |Cite
|
Sign up to set email alerts
|

Only the N-Terminal Domain of FtsK Functions in Cell Division

Abstract: Deletion of ftsK results in the inhibition of cell division, but this inhibition can be reversed by a plasmid carrying only the first ∼17% of ftsK. The division block can be suppressed in most mutants by deletion of dacA, which codes for the d-alanine:d-alanine carboxypeptidase PBP5, or in all mutants by overexpression of ftsN. Overexpression of ftsK inhibits cell division and the formation of FtsZ rings. This division block is not due to the induction of either the SOS or the heat shock regulons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
2
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 26 publications
5
90
2
2
Order By: Relevance
“…pcI P22 or pcI 434 . phenotype of the mutant described in Draper et al (1998), could explain the discrepancy between our result and that described previously. As far as the FtsK fragment 725-1329 is concerned (Fig.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…pcI P22 or pcI 434 . phenotype of the mutant described in Draper et al (1998), could explain the discrepancy between our result and that described previously. As far as the FtsK fragment 725-1329 is concerned (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…FtsK structural analysis showed that the protein consists of an N-terminal domain (about 200 residues) with several predicted membrane-spanning regions involved in cell division (Draper et al, 1998;Wang & Lutkenhaus, 1998;Yu et al, 1998), a proline-glutamine-rich domain (linker region of about 500 residues) and a C-terminal domain with a nucleotide-binding consensus sequence of about 500 amino acids involved in DNA segregation (Yu et al, 1998;Steiner et al, 1999;Bigot et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are consistent with a defect in membrane fusion, but it has also been suggested that FtsK is needed for the final stages of peptidoglycan synthesis because FtsK deletions can be rescued by deleting dacA, which encodes a carboxypeptidase (Draper et al, 1998). FtsK deletions can also be suppressed by overexpression of FtsN (Draper et al, 1998), the structure of which has revealed a potential peptidoglycan binding site (Yang et al, 2004).…”
Section: The Z Ring Undergoes Rapid Turnoversupporting
confidence: 76%
“…While an ftsK depletion strain forms smooth filaments, indicating that FtsK is required to initiate cytokinesis, several point and truncation mutants form deep constrictions, as if these forms of FtsK are specifically defective in the final stages of septum closure (Begg et al, 1995;Diez et al, 1997;Wang and Lutkenhaus, 1998;Yu et al, 1998a). These observations are consistent with a defect in membrane fusion, but it has also been suggested that FtsK is needed for the final stages of peptidoglycan synthesis because FtsK deletions can be rescued by deleting dacA, which encodes a carboxypeptidase (Draper et al, 1998). FtsK deletions can also be suppressed by overexpression of FtsN (Draper et al, 1998), the structure of which has revealed a potential peptidoglycan binding site (Yang et al, 2004).…”
Section: The Z Ring Undergoes Rapid Turnovermentioning
confidence: 75%